2015
DOI: 10.1103/physrevb.91.224425
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of a kagome lattice with magnetic dipolar interactions

Abstract: The results of extensive Monte Carlo simulations of classical spins on the two-dimensional kagome lattice with only dipolar interactions are presented. In addition to revealing the six-fold degenerate ground state, the nature of the finite-temperature phase transition to long-range magnetic order is discussed. Low temperature states consisting of mixtures of degenerate ground state configurations separated by domain walls can be explained as a result of competing exchange-like and shape anisotropy-like terms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
1
21
1
Order By: Relevance
“…[2][3][4][5] and references therein), and, over decades, a number of theoretical studies, based on Renormalization group techniques, has addressed interaction models containing both dipolar and short-range isotropic or anisotropic exchange interactions (see, e.g., Refs [2,[6][7][8][9][10][11]); on the other hand, lattice models involving only the longrange dipolar term have also long been studied by various approaches, including spin-wave treatments and simulation (see, e.g., Refs. [12][13][14][15][16][17][18][19], and others quoted in the following). While the former references have dealt with the resulting critical behavior, including the crossover between isotropic dipolar universality class (when the dipolar term is dominant) and the Heisenberg one (corresponding to nearest-neighbor exchange interactions only), the later ones were mostly focused on the ground state of the magnetically ordered phase; in addition, a survey of relevant rigorous mathematical results can be found in [20].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[2][3][4][5] and references therein), and, over decades, a number of theoretical studies, based on Renormalization group techniques, has addressed interaction models containing both dipolar and short-range isotropic or anisotropic exchange interactions (see, e.g., Refs [2,[6][7][8][9][10][11]); on the other hand, lattice models involving only the longrange dipolar term have also long been studied by various approaches, including spin-wave treatments and simulation (see, e.g., Refs. [12][13][14][15][16][17][18][19], and others quoted in the following). While the former references have dealt with the resulting critical behavior, including the crossover between isotropic dipolar universality class (when the dipolar term is dominant) and the Heisenberg one (corresponding to nearest-neighbor exchange interactions only), the later ones were mostly focused on the ground state of the magnetically ordered phase; in addition, a survey of relevant rigorous mathematical results can be found in [20].…”
Section: Introductionmentioning
confidence: 96%
“…Some similar studies have been published only recently in Refs. [18,19], and have addressed the ground state of a model of pure dipolar interaction considering different types of lattices; the magnetic properties of the ground state were determined for each lattice structure.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported here is limited to the square lattice model and therefore the degeneracy that destroys the ordered state when K = K c arises only from the competition between the interactions. However, in view of recent advances in methods for fabricating ultra-thin films, studies of dynamics in systems with structural frustration will also be of interest (see, e.g., the work by Holden et al [28] and Maksymenko et al [29] and references therein).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…We now briefly consider the case when MSs are initially oriented to minimize dipolar energy, and make 120 degrees with respect to each other [49]. Fig.…”
Section: B Triangular Order: When the Internal Structure Mattersmentioning
confidence: 99%